Effect of micronutrient iron on bioactive compounds isolated from cryptophytes - Abidizadegan, Maryam; Blomster, Jaanika; Peltomaa, Elina (Frontiers in Plant Science, 2023)
Iron is one of the important micronutrients affecting algal growth due to its fundamental role in the physiological processes, including photosynthetic electron transport, respiration, and nitrogen fixation. In this study, the effect of different iron levels on growth and the production of bioactive compounds (phycoerythrin (PE), extracellular polymeric substances (EPS), and phenolic compounds (PCs)) of five cryptophyte strains were investigated. Also, the antioxidant capacity of the bioactive compounds was explored. The results showed species-specific responses to the impact of iron on growth of cryptophytes and accumulation of bioactive compounds. The growth rates of C. pyrenoidifera and Cryptomonas sp. varied significantly at different iron levels, and a reduction in the PE content was observed for several cryptophytes cultured at the highest iron level. However, no significant differences were detected in EPS content at different iron levels. Differences in PC contents of C. pyrenoidifera and Cryptomonas sp. at medium iron level were statistically significant compared with the other two treatments. The results also revealed species-specific differences in antioxidant activity at different iron levels; each studied strain followed its own pattern in response to change in iron level, and each bioactive compound had a different antioxidant activity. Overall, however, PCs demonstrated higher antioxidant activity than PE and EPS. In summary, iron has an impact on growth, bioactive compound accumulation, and antioxidant activity. However, the speciesspecific responses to changes in iron level should not be ignored when modifying culture conditions for optimal harvest of bioactive compounds.